Mitral valve replacement with aortic heterografts in humans - Ionescu, M. I. (1967)
The complications associated with the implantation of prosthetic valves and the experimental attempts to graft the mitral valve are described. Because of the disadvantages connected with the use of artificial valves and as the experimental methods of grafting the mitral valve did not prove satisfactory for clinical use, the authors developed a technique for mitral valve replacement using heterologous aortic valves—reinforced by a semirigid Teflon ring—placed above the mitral annulus inside the atrial cavity. The technique of collecting, preparing, and inserting these grafts is described in detail. Using this method, seven patients with mitral incompetence or mitral disease were operated upon between February and April, 1967. One patient died five weeks after the operation from bacterial endocarditis in a period of severe hospital infection with staphylococcus. The other six patients had a very good clinical result immediately after surgery. At the present time they are symptom-free and have normal heart sounds. Clinical and experimental data are discussed concerning the long-term fate of aortic heterografts in the mitral position.